The Relationship between Anxiety Symptoms and Smoking AmongAdolescents in Samarinda - Vicca Yulia Insany; Riyan Ningsih; Akhmad Azmiardi (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Adolescents are a vulnerable population for both anxiety disorders and health risk behaviors such as smoking, including the use of electronic cigarettes. Anxiety symptoms in adolescents are thought to contribute to earlier smoking initiation. Objective : This study aimed to examine the relationship between anxiety symptoms and smoking behavior among adolescents in Samarinda Research Methods/ Implementation Methods : This cross-sectional study was conducted in the working area of Baqa Primary Healthcare Center, Samarinda, in 2025. A total of 212 senior high school students were selected using a total sampling technique. Smoking behavior data were collected using a smoking behavior screening questionnaire. Anxiety symptoms were measured using the Mini MINDHEAR Youth Scale V.1 (anxiety subscore). Data were analyzed using univariate and bivariate analysis with the Chi-Square test Results : Most respondents were aged 15 to 17 years. Among the smokers, 40 participants were male (81%) and 9 were female (19%); 29 respondents (59%) reported smoking conventional tobacco cigarettes, while 20 respondents (40%) used electronic cigarettes. The proportion of smoking (tobacco/e-cigarettes) among respondents with anxiety symptoms was 33.9%, compared to 19.2% among those without anxiety symptoms. There was a statistically significant association between anxiety symptoms and smoking behavior (p = 0.025; PR = 2.157; 95 percent CI = 1.091–4.264). Conclusion/Lesson Learned : There is a significant relationship between anxiety symptoms and smoking behavior among students. These findings highlight the importance of mental health screening and intervention within School Health Programs (UKS), Adolescent Integrated Community Health (Posyandu Remaja), and Smoking Cessation Program (UBM